Soft Tissue Sarcomas in Cats: A Comparative Review on Injection-Site and Non-Injection-Site Sarcomas - Wright, Carolina (2025)
Malignant tumors originating in connective tissue cells of mesenchymal origin are considered soft tissue sarcomas. Soft tissue sarcomas represent between 7%-9% of malignant tumors of the skin and subcutaneous tissue in cats. Among the sarcomas affecting cats, there is a specific group known as inoculation site-associated sarcomas. Sarcomas that do not occur at sites typically used for the injection of substances will be classified in this review as non-inoculation site-associated sarcomas. Fibrosarcoma is the most common histological type and accounts for 80–92% of soft tissue sarcomas in cats. The prevalence of non-inoculation site sarcomas in cats is 17 in 100,000, while the prevalence of inoculation site sarcomas is estimated to be between 1 in 1,000 and 1 in 10,000 vaccinated cats. The aim of the present study was to compare the information present in the available literature in relation to the morphological characteristics, biological behavior, pathogenesis, diagnosis and treatment of both inoculation site-associated and non-associated sarcomas in cats. A more complete understanding of these neoplasms and their differences is essential to deepen the understanding of their genesis and progression. A better understanding could lead to the development of more effective intervention strategies that improve the quality of life and survival of cats affected by these sarcomas.